Selenium Deficiency as a Risk Factor for Development of Anemia - Tsvetelina Petkova-Marinova; Boryana Ruseva; Bisera Atanasova (Journal of Biomedical & Clinical Research, 2017)
Anemia is an important public health problem worldwide. Although iron (Fe) deficiency is considered the main factor in the pathogenesis of anemia, only 40-60% of anemia cases are responsive to Fe supplementation. Considerable data exist that other micronutrient deficiencies, such as selenium (Se), could be possible causes of anemia. The issue of Se deficiency as a risk factor for the development of anemia is of particular interest to our country since the Balkan region is known by a low Se content of soils. The aim of the study was to examine the contemporary conception of the influence of Se deficiency on the development of anemia by a review of the scientific literature. Most animal studies have shown a significant relation between Se deficiency and anemia, but one study indicates that there is no impact of Se deficiency on the hematological parameters. Associations of low serum Se with anemia have been found in a number of human studies including subjects of various age groups and pathological conditions. Three possible biological mechanisms have been suggested for the involvement of Se deficiency in the development of anemia: increased oxidative stress, modulation of inflammation through induction of interleukin-6, and increased expression of heme oxygenase-1. A more categorical clarification of the relationships between Se deficiency and development of anemia is needed with respect to appropriate trace element supplementation in cases of anemia with insufficient or absent therapeutic response to Fe treatment.